Hubungan Implementasi Sistem Manajemen ISO 9001-2015 terhadap Peningkatan Standar Mutu Produk Baja Tulangan di Jakarta - Lestiningsih, Amin Setio; -, Sabil Sabil; -, Lukman Hakim; Widodo, Dwiyatmoko Puji (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2023)
The purpose of this study was to analyze the effect of the implementation of the ISO 9001-2015 management system on improving the quality standards of bridging steel products, this research method is quantitative. Data collection through questionnaires was carried out using simple random sampling technique and the number of respondents was 539, consisting of 493 executive employees and 27 respondents who were elements of the leadership of a reinforcing steel company in Jakarta. Data processing uses SPSS version 21 and uses the help of Microsoft Excel. The results of this study conclude that there is a strong and significant relationship between the ISO 9001: 2015 Quality Management System and the Reinforcing Steel Product Quality Standards in Jakarta. Taking into account the Pearson correlation value, it can be said that the relationship between both variables are very strong and dominant. The ISO 9001: 2015 Quality Management System that is positive in this case is the desire to be appreciated in carrying out work so that it can produce Quality Standards for Reinforcing Steel Products in accordance with applicable standards. The novelty of this research is the influence of the quality management system which has a significant effect on the quality standards of steel allowances. Keywords: ISO Management System, Quality Standards